Hepatic steatosis is associated with anthropometry, cardio‐metabolic disease risk, sex, age and urbanisation, but not with ethnicity in adult Kenyans. Issue 1 (7th November 2021) - Kastberg, Sophie E.; Lund, Helene S.; De Lucia‐Rolfe, Emanuella; Kaduka, Lydia U.; Boit, Michael K.; Corpeleijn, Eva; Friis, Henrik; Bernard, Sophie; Paquette, Martine; Baass, Alexis; Rasmussen, Jon J.; Christensen, Dirk L.
Abstract: Objective: We aimed to determine the associations of non‐alcoholic fatty liver disease (NAFLD) with cardio‐metabolic risk factors for diabetes in adult Kenyans. Methods: A cross‐sectional study was undertaken among rural and urban Kenyans of different ethnic origin. Ultrasonography scanning (USS) methods were used for the assessment of hepatic fat accumulation for NAFLD assessment and abdominal fat distribution, and simple anthropometry measurements were performed. All participants underwent a 2‐h oral glucose tolerance test, and biochemical, haemodynamic and lifestyle data were obtained. Multivariate logistic regression analyses were used to assess sex, age, residency and ethnic differences in the association between NAFLD and various metabolic parameters. Results: In total, 743 individuals (59.1% women) with a mean age of 38.0 (range 18–68) years participated in the study. Overall, 118 individuals (15.9%) had NAFLD, of whom 94.1% had mild steatosis. Age >40 years was significantly associated with having NAFLD compared with <30 years of age with no difference found in NAFLD between ethnic groups (Luo, Kamba, Maasai). All body composition and clinical measurements were associated with NAFLD ( p  < 0.045 for OR). Conclusion: Finding lower odds for NAFLD in men was unexpected, as was the lack of differences in NAFLD among the ethnic groups, while higher odds for NAFLD with increasing age and in urban vs. rural populations was expected. Especially the sex‐specific results warrant further studies in black African populations on biology of body composition for having NAFLD, and whether this translates into insulin resistance and higher risk of diabetes and consequently cardiovascular disease in black African women.